Learning Multimedia Development Using Articulate Storyline for Students - Nugroho, Fandi; Arrosyad, Muhammad Iqbal (Universitas Pendidikan Ganesha, 2020)
The implementation of learning in elementary schools is very limited to learning media and more teacher-centred learning. This study aims to develop multimedia learning using articulated storylines that are feasible and effective for fourth-grade students of SD Muhammadiyah Pangkalpinang. This type of research is Research and Development (R&D). This research development stage refers to the Alessi & Trollip development model, which is divided into four stages, namely: (1) planning; (2) design; (3) product development, and (4) evaluation. Determination of the feasibility level based on the validation test of media and material experts and testing to 6 students through a questionnaire. Determination of the level of effectiveness based on pre-test and post-test data to 30 students. The results showed that the average feasibility level of the assessment percentage by the media expert validator was 82.5% with the